Materiales reciclados y aprendizaje significativo en los niños de la Institución Educativa Inicial N°728, Ramón Castilla 2023 - Tamani Correa de Ramirez, Yliana Jessica (2024)
The purpose of this study was to examine the association between recycled materials and meaningful learning in the children of the Institución Educativa Inicial N°728 Ramón Castilla in the year 2023. The research methodology adopted was quantitative and relational in nature, with a specific non-experimental, correlational and transectional approach. The selection of the most appropriate design for this study leaned towards non-experimental research. The total population (N) included 128 children from the institution. We chose to select a sample size identical to the population size, mainly due to practical considerations. Data collection was carried out through observation, supported by a specific checklist, together with questionnaires that were previously validated by experts in the field. The results obtained through the Pearson correlation analysis a coefficient of 0.768, evidencing a considerable correlation between both variables. Consequently, the research hypothesis is confirmed, concluding that the use of recycled materials has a significant relationship with the acquisition of significant learning in children belonging to the Initial Educational Institution N°728 Ramón Castilla in the year 2023.